The Effect Of Hand Exercise On Grip Strength, Forearm Circumference, Diameter Of Vein, Blood Flow Volume And Velocity In Patient Who Underwent Arteriovenous Fistula Surgery And On Routine Haemodialysis - Jufri Febriyanto Poetra; Andriati Andriati; Dewi Poerwandari (Surabaya Physical Medicine and Rehabilitation Journal, 2019)
Background: The arteriovenous fistula (AVF) is considered the gold standard for haemodialysis access. The fistula needs time to be mature and functional. Maturation process respond to increases in blood flow. Exercise stimulates vascular response as such an increase of blood flow. Aims: The purpose of this study is to determine the effectiveness of hand exercise in increasing grip muscle performance, and its effectiveness in supporting maturation process of fistula.Methods: This experimental study done on 14 patients underwent AVF procedure and on routine haemodialysis. Randomly, 7 subjects allocated on intervention group by doing hand exercise using hand gripper (HG) for 5 weeks, and 7 subjects allocated as control group without introduction to hand gripper. Grip strength and forearm circumference were measured before and after 5 weeks of intervention. Cephalic vein diameter, blood flow volume and velocity were measured using Doppler USG on AVF arm. The comparison of intervention effects between groups treatment were analyzed based on effect size (ES).Results: Grip strength and forearm circumference increased significantly on intervention group before and after exercise intervention (p<.001, p=.001). Cephalic vein diameter and blood flow were increased significantly in this group (p=.027, p=.033). Blood flow velocity showed no difference before and after exercise intervention. Significant results were found on increased grip strength, forearm circumference, cephalic vein diameter and blood flow volume in comparison between treated group (p<.001; ES=.94, p<.001; ES=.4, p=.046; ES=.84, p=.035; ES=.53). There were no differences on cephalic vein blood flow velocity between these two groups.Conclusion: Five weeks hand exercise were effective to increase grip strength, forearm circumference, cephalic vein diameter and blood flow volume, nonetheless ineffective to increase cephalic vein blood flow velocity in post AVF procedure patients with routine haemodialysis.